The Economics of Joint Ventures in Less Developed Countries - Svejnar, Jan; Smith, Stephen C. (Quarterly Journal of Economics, 1984)
The paper examines the microeconomic (partial equilibrium) behavior of joint ventures established between transnational corporations and domestic partners in less developed countries. It focuses on issues relating to resource allocation and profit distribution under various institutional scenarios. The analysis places special emphasis on the role of bargaining power, transfer pricing, stock ownership, and profit shares of the parties, and the responsiveness of joint ventures to national development goals. Some of the results apply to wholly owned subsidiaries of transnational corporations, local firms, and licensing arrangements, which emerge as special cases.